2012
DOI: 10.1002/sres.2128
|View full text |Cite
|
Sign up to set email alerts
|

Equifinality in Project Management Exploring Causal Complexity in Projects

Abstract: Surveys reveal that the majority of innovation projects do not achieve their goals and waste resources. Notorious examples are the National Health Service's National Programme for IT project and many multibillion European Union funded projects. Academics and practitioners suggest that this failure is because conventional project management methods fail to capture the serendipitous, evolutionary and experimental nature of complex innovation projects. Results from previous research based on European Union health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 65 publications
0
32
0
21
Order By: Relevance
“…Liu and Leitner (2012) similarly find that managers respond to complexities by being ambidextrous in their practices -using strategies of both exploitation (applying known or planned responses to dealing with structural and socio-political complexities) and exploration (responding to emergent complexities) (see also Turner et al, 2014;Turner, Maylor and Swart, 2015). Kapsali (2013) also notes a move against the 'engineering' approach to project management (deconstruction, planning and control responses) and argues for the value of systems thinking in this context. Similarly, Staadt (2012) discusses the challenge of socio-political complexities in projects and supports the use of a Soft Systems Methodology (SSM) for sensemaking in this context.…”
Section: Responses To Complexitiesmentioning
confidence: 99%
“…Liu and Leitner (2012) similarly find that managers respond to complexities by being ambidextrous in their practices -using strategies of both exploitation (applying known or planned responses to dealing with structural and socio-political complexities) and exploration (responding to emergent complexities) (see also Turner et al, 2014;Turner, Maylor and Swart, 2015). Kapsali (2013) also notes a move against the 'engineering' approach to project management (deconstruction, planning and control responses) and argues for the value of systems thinking in this context. Similarly, Staadt (2012) discusses the challenge of socio-political complexities in projects and supports the use of a Soft Systems Methodology (SSM) for sensemaking in this context.…”
Section: Responses To Complexitiesmentioning
confidence: 99%
“…They highlighted a need to develop practitioners who are adaptable and pragmatic (Crawford et.al., 2006, p. 724), (Winter et al 2006, p. 646). Notwithstanding significant number of certified project managers, projects could still be seen to be failing with regularity, and unfortunately this position does not appear to be changing (Dalcher, 2003;Kapsali, 2013;The Standish Group, 2009, 2013Thomas and Mengel, 2008). Crawford et.…”
Section: Formal and Informal Discussion With Staffmentioning
confidence: 99%
“…The uncertainty and unpredictability induced by the combined effects of such factors pose a variety of challenges for successful project management [23,24]. Experience suggested that the interdependencies among the project components and project context are more complicated.…”
Section: Project Complexity and Attributesmentioning
confidence: 99%